Breed and timepoint-based analysis of chicken harderian gland transcriptome during Newcastle disease virus challenge - Vanamamalai, Venkata Krishna; Priyanka, E.; Kannaki, T. R.; Sharma, Shailesh (Frontiers in Molecular Biosciences, 2024)
Introduction: Newcastle disease is a highly infectious disease caused by the Newcastle Disease Virus (NDV) and has a devastating financial impact on the global chicken industry. It was previously established that Leghorn and Fayoumi breeds of chicken exhibit variable resistance against NDV infection. The harderian gland is the less studied tissue of the chicken, known to play an essential role in the immune response. Methods: Our previous study, we reported differential gene expression and long noncoding RNAs (lncRNAs) between challenged and non-challenged chickens in the Harderian gland transcriptomic data. Now, we report the analysis of the same data studying the differential expression patterns between Leghorn and Fayoumi and between different timepoints during disease. First, the pipeline FHSpipe was used for identification of lncRNAs, followed by differential expression analysis by edgeR (GLM), functional annotation by OmicsBox, co-expression analysis using WGCNA and finally validation of selected lncRNAs and co-expressing genes using qRT-PCR. Results: Here, we observed that Leghorn showed a higher number of upregulated immune-related genes than Fayoumi in timepoint-based analysis, especially during the initial stages. Surprisingly, Fayoumi, being comparatively resistant, showed little difference between challenged and non-challenged conditions and different time points of the challenge. The breed-based analysis, which compared Leghorn with Fayoumi in both challenged and non-challenged conditions separately, identified several immune-related genes and positive co-expressing cis lncRNAs to be upregulated in Fayoumi when compared to Leghorn in both challenged and non-challenged conditions. Discussion: The current study shows that Leghorn, being comparatively more susceptible to NDV than Fayoumi, showed several immune-related genes and positive co-expressing cis lncRNAs upregulated in challenged Leghorn when compared to non-challenged Leghorn and also in different timepoints during challenge. While, breed-based analysis showed that there were more upregulated immune genes and positive cis-lncRNAs in Fayoumi than Leghorn. This result clearly shows that the differences in the expression of genes annotated with immune-related GO terms and pathways, i.e., immune-related genes and the co-expressing cis-lncRNAs between Leghorn and Fayoumi, and their role in the presence of differences in the resistance of Leghorn and Fayoumi chicken against NDV. Conclusion: These immune-genes and cis-lncRNAs could play a role in Fayoumi being comparatively more resistant to NDV than Leghorn. Our study elucidated the importance of lncRNAs during the host defense against NDV infection, paving the way for future research on the mechanisms governing the genetic improvement of chicken breeds.